Acute care and secondary prevention of stroke with newly detected versus known atrial fibrillation - Wang, Ruihao; Macha, Kosmas; Haupenthal, David; Gaßmann, Luise; Siedler, Gabriela; Stoll, Svenja; Fröhlich, Kilian; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd (European Journal of Neurology, 2022)
Background and purpose: Atrial fibrillation (AF) in stroke patients can be classified as either “known AF” (KAF), defined as AF confirmed before stroke onset, or “AF detected after stroke” (AFDAS), defined as AF diagnosed after stroke onset. While KAF is considered primarily cardiogenic, AFDAS includes patients with stroke-triggered neurogenic arrhythmias. This study aimed to investigate the clinical course of stroke, functional outcomes and the value of oral anticoagulation (OAC) for secondary prevention according to AF subtype. Methods: Acute ischemic stroke patients were consecutively enrolled and AF was classified as AFDAS or KAF. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) and 3-month functional outcomes were measured on the modified Rankin scale. Inverse probability weighting was applied to adjust for baseline confounders in patients with AFDAS and KAF. Multivariate logistic regression models were calculated to investigate the value of OAC for secondary prevention. Results: A total of 822 stroke patients with AF were included, of whom 234 patients (28.5%) had AFDAS. AFDAS patients had a lower prevalence of coronary artery disease, heart failure, and sustained AF, but higher rates of large vessel occlusion compared to KAF patients. NIHSS scores were lower in patients on pre-stroke anticoagulation. OAC for secondary prevention was associated with favorable 3-month functional outcome (odds ratio 7.60, 95% confidence interval 3.42–16.88) independently of AF subtype. The rate of stroke recurrence did not differ significantly. Conclusions: Clinical characteristics suggest that AFDAS might comprise a distinct pathophysiological and clinical entity among stroke patients with AF. The benefit of anticoagulation for secondary prevention was not affected by AF subtype.
CRIS-Team Scopus Importer:2022-04-22
Keywords: acute ischemic stroke; atrial fibrillation detected after stroke; known atrial fibrillation; modified Rankin scale; oral anticoagulation; stroke recurrence

Atrial Fibrillation Detected before or after Stroke: Role of Anticoagulation - Lyrer, Flurina; Zietz, Annaelle; Seiffge, David J.; Koga, Masatoshi; Volbers, Bastian; Wilson, Duncan; Bonetti, Bruno; Schaedelin, Sabine; Gensicke, Henrik; Yoshimura, Sohei; Macha, Kosmas; Ambler, Gareth; et al. (Annals of Neurology, 2023)
Background: Atrial fibrillation (AF) known before ischemic stroke (KAF) has been postulated to be an independent category with a recurrence risk higher than that of AF detected after stroke (AFDAS). However, it is unknown whether this risk difference is confounded by pre-existing anticoagulation, which is most common in KAF and also indicates a high ischemic stroke recurrence risk. Methods: Individual patient data analysis from 5 prospective cohorts of anticoagulated patients following AF-associated ischemic stroke. We compared the primary (ischemic stroke recurrence) and secondary outcome (all-cause death) among patients with AFDAS versus KAF and among anticoagulation-naïve versus previously anticoagulated patients using multivariable Cox, Fine-Gray models, and goodness-of-fit statistics to investigate the relative independent prognostic importance of AF-category and pre-existing anticoagulation. Results: Of 4,357 patients, 1,889 (43%) had AFDAS and 2,468 (57%) had KAF, while 3,105 (71%) were anticoagulation-naïve before stroke and 1,252 (29%) were previously anticoagulated. During 6,071 patient-years of follow-up, we observed 244 recurrent strokes and 661 deaths. Only pre-existing anticoagulation (but not KAF) was independently associated with a higher hazard for stroke recurrence in both Cox and Fine-Gray models. Models incorporating pre-existing anticoagulation showed better fit than those with AF category; adding AF-category did not result in better model fit. Neither pre-existing anticoagulation nor KAF were independently associated with death. Conclusion: Our findings challenge the notion that KAF and AFDAS are clinically relevant and distinct prognostic entities. Instead of attributing an independently high stroke recurrence risk to KAF, future research should focus on the causes of stroke despite anticoagulation to develop improved preventive treatments. ANN NEUROL 2023.
CRIS-Team Scopus Importer:2023-04-28

Oral Anticoagulants in the Oldest Old with Recent Stroke and Atrial Fibrillation - Polymeris, Alexandros A.; Macha, Kosmas; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Cappellari, Manuel; Schaedelin, Sabine; Zietz, Annaelle; Peters, Nils; Seiffge, David J.; Haupenthal, David; Gaßmann, Luise; et al. (Annals of Neurology, 2021)
Objective To investigate the safety and effectiveness of direct oral anticoagulants (DOAC) versus vitamin K antagonists (VKA) after recent stroke in patients with atrial fibrillation (AF) aged >= 85 years. Methods Individual patient data analysis from seven prospective stroke cohorts. We compared DOAC versus VKA treatment among patients with AF and recent stroke (<3 months) aged >= 85 versus <85 years. Primary outcome was the composite of recurrent stroke, intracranial hemorrhage (ICH) and all-cause death. We used simple, adjusted, and weighted Cox regression to account for confounders. We calculated the net benefit of DOAC versus VKA by balancing stroke reduction against the weighted ICH risk. Results In total, 5,984 of 6,267 (95.5%) patients were eligible for analysis. Of those, 1,380 (23%) were aged >= 85 years and 3,688 (62%) received a DOAC. During 6,874 patient-years follow-up, the impact of anticoagulant type (DOAC versus VKA) on the hazard for the composite outcome did not differ between patients aged >= 85 (HR >= 85y = 0.65, 95%-CI [0.52, 0.81]) and < 85 years (HR<85y = 0.79, 95%-CI [0.66, 0.95]) in simple (p(interaction) = 0.129), adjusted (p(interaction) = 0.094) or weighted (p(interaction) = 0.512) models. Analyses on recurrent stroke, ICH and death separately were consistent with the primary analysis, as were sensitivity analyses using age dichotomized at 90 years and as a continuous variable. DOAC had a similar net clinical benefit in patients aged >= 85 (+1.73 to +2.66) and < 85 years (+1.90 to +3.36 events/100 patient-years for ICH-weights 1.5 to 3.1). Interpretation The favorable profile of DOAC over VKA in patients with AF and recent stroke was maintained in the oldest old. ANN NEUROL 2021
CRIS-Team WoS Importer:2021-12-10

STROKE CARE PERFORMANCE MEASURES DURING THE COVID-19 PANDEMIC - OVER THE WAVES - Gaßmann, Luise; Haupenthal, David; Kallmünzer, Bernd; Köhn, Julia; Schwab, Stefan; Kuramatsu, Joji (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18